Utopian feminism : women's movements in fin-de-siècle Vienna - Anderson, Harriet, 1957- (Yale University Press, 1992)
"The Viennese women's movement at the turn of the century made valuable and original contributions to social reform, feminist ideology, and artistic and intellectual trends of the era. This book--the first to examine this movement in depth--discusses its historical development, the activities, personalities, and writings of its middle-class members, and the Viennese culture and politics in which it flourished. Harriet Anderson argues that the movement was not primarily focused on women's rights but was a utopian endeavor that sought to bring about the moral reform of society through women's efforts. She discusses the numerous women's associations that sprang up at the turn of the century, groups that focused on women's education, legal reform, state-controlled prostitution, and anti-Semitism, among other issues. Examining the General Austrian Women's Association in particular, Anderson reconstructs its history and describes the ideals that informed it, the personal loves and animosities of its leading figures, and the conflicts in which it engaged up to its decline in the chaos of the First World War. She next critically analyzes the feminists' theoretical writings, placing them in their intellectual contexts, investigating their poetics, and showing how they were shaped by various utopian visions. Finally she discusses the women's fictional works, identifying two main groups of feminist writers, one that wrote mainly moral texts supporting the prevalent middle-class code of conduct, and the other that sought to investigate psychological mechanisms and expose deep-rooted oppression."--